Implementasi Nilai-Nilai Religius Pancasila Dan Wawasan Pancasila Dalam Sekolah Berbasis Pesantren - Uswatun Hasanah; Ludfi Arya Wardana; Hamdan Amrullahc (CV. ITTC INDONESIA, 2023)
Pancasila is the ideology of the Indonesian nation. Religious values are a manifestation of attitudes that demonstrate a quality of life that is inseparable from religious teachings. As long as Pancasila is viewed as something positive and remains distant from endangering the Indonesian nation, it is considered to be in line with religious norms. The integration of religious values from Pancasila with Pancasila's perspective in pesantren-based schools provides significant benefits for students. They not only receive a strong religious education but are also equipped with a solid understanding of national unity, becoming agents of change that bring harmony to society. The Pancasila perspective serves as guidance in responding to social dynamics, being open to criticism, and serving as a common point, focus, and goal for fostering collective awareness of the national system. This research aims to describe the implementation of religious values from Pancasila and the Pancasila perspective in pesantren-based schools. Pesantren is a traditional educational institution with distinctive characteristics that combine religious and general education. Pancasila, as the foundation of the Indonesian state, emphasizes religious values and national perspectives that complement each other. In this context, pesantren can play a role as an educational institution that bridges the gap between religious and general education, producing individuals who are well-integrated into national life.